Understanding migraine and other headaches - Anne MacGregor British Medical Association (Family Doctor Publications, 2010)
Designed and written specifically for the general reader, the books in this series provide essential reading for sufferers and those who seek to understand and support them. This title focuses on migraines & other headaches.